Physical and mathematical modeling of Earth and environment processes (2018) : 4th International Scientific School for Young Scientists, Ishlinskii Institute for Problems in Mechanics of Russian Academy of Sciences /: 4th International Scientific School for Young Scientists, Ishlinskii Institute for Problems in Mechanics of Russian Academy of Sciences. (2019) - Unknown
No abstract available